Development and Application of a Pragmatic Algorithm to Guide Definitive Carbapenemase Testing to Identify Carbapenemase-Producing Pseudomonas aeruginosa - Christian M. Gill; Tomefa E. Asempa; David P. Nicolau (MDPI AG, 2020)
A minimum inhibitory concentration (MIC) derived algorithm, predictive of carbapenemase production, was developed using a challenge set (n = 92) of Pseudomonas aeruginosa (PA), including carbapenemase-producing (CP), cephalosporinase and/or efflux/porin mutation, and wild-type isolates. Broth microdilution MICs to clinically relevant anti-pseudomonal agents were utilized. The algorithm was applied to 1209 clinical PA isolates from a US surveillance program. Confirmatory genotypic (Xpert® Carba-R assay) and phenotypic (mCIM/eCIM) testing for carbapenemases was conducted on algorithm-derived isolates. With the algorithm, carbapenem resistance alone resulted in poor specificity to identify CP-PA (54%) within the challenge set of isolates. Inclusion of cefepime, ceftazidime, and piperacillin/tazobactam non-susceptibility resulted in a specificity of 66%. Ceftolozane/tazobactam resistance further improved specificity (89%). Of the 1209 isolates, 116 met criteria (carbapenem-resistant and non-susceptibility to cefepime, ceftazidime, and piperacillin/tazobactam) for confirmatory testing. Carba-R and mCIM/eCIM identified five (all blaVIM-positive) and seven carbapenemase-producing isolates, respectively. This MIC algorithm combined with genotypic/phenotypic carbapenemase testing is a pragmatic and streamlined approach to identify CP-PA.